Determination of the transition strategies to a sustainable and resilient city-region food system using the AHP-SWOT-TOWS methodology for Istanbul - Seckin, Ebru; Ozdil, Guzin Guliz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
Access to healthy food is a topic that has been largely discussed in the literature for about 20-30 years. In many studies, it has been emphasised that the connections between the urban and rural areas should be continuous and strong. The Covid-19 pandemic has shed light on the importance of the issue of feeding the cities and has also revealed the problems in the way the existing system functions. Based on this, the aim of this article is to understand how the food system of Istanbul was affected by the Covid-19 global epidemic and also discuss what should be done to create a resilient and sustainable food system in cities. Within the scope of this research, a strength, weakness, opportunity, threat (SWOT) analysis was conducted to determine the factors affecting the resilience of the food system in Istanbul. Then, the SWOT criteria were weighted using the analytical hierarchy process (AHP) method. The weighted criteria were matched in a TOWS matrix, and strategies to increase the resilience of the food system in Istanbul against shocks and risks were developed. The analysis is based on interviews conducted with industry experts and actors. As a result, it is observed that the long supply chain is dominant in Istanbul and there is a need to strengthen the direct and spatial relations between the producer and consumer. Therefore, it is vital to address the food system while considering the spatial dimension, to strengthen the link between urban and rural areas, to increase the resilience of the food system against shocks as well as to ensure the accessibility of food products within shorter distances.
Keywords: AHP-SWOT-TOWS analysis; Covid-19; food system; resilience; short supply chains; urban-rural relationship; TOOL; Architecture